Development of PMMA-CeO2 anticorrosive hybrid coatings with self-healing property - Rodrigues, Mariana S. [UNESP]; Souza, Thiago A.C. [UNESP]; Harb, Samarah V.; Trentin, Andressa [UNESP]; Hammer, Peter [UNESP] (My University, 2021)
Organic-inorganic hybrids are a new class of materials considered as a nontoxic alternative to replace noxious chromate-based anticorrosive coatings. In this context, hybrid nanocomposites based on poly(methyl methacrylate) (PMMA) and cerium oxide nanoparticles, were developed in order to obtain high performance anti-corrosion coatings. Initially, CeO2 nanoparticles were synthetized by the reaction between LiOH and Ce(NO3)3, varying the molar ratio of these reagents, and then the reaction of methyl methacrylate and 2-hydroxyethyl methacrylate was performed to obtain PMMA-CeO2 hybrids. The synthesized materials were deposited by dip-coating on A1020 carbon steel and AA7075 aluminum alloy substrates yielding homogeneous coatings. Dynamic light scattering was used to study the formation of CeO2 nanoparticles, while the PMMA-CeO2 coatings were characterized by thickness measurements, optical microscopy, atomic force microscopy, thermogravimetric analysis and electrochemical impedance spectroscopy. The results showed that lower amount of LiOH leads to the formation of smaller CeO2 nanoparticles (~5 nm), improved thermal stability (219 °C) and excellent anticorrosive performance in 3.5% NaCl, with a low-frequency impedance modulus up to 400 GΩ cm2 and self-healing ability after pitting.
Keywords: Anticorrosive coating; Organic-inorganic hybrid; Self-healing; Sol-gel process